Waste : A New Media Primer - Simanowski, Roberto (Book collections on Project MUSE., 2018)
"Series of essay chapters (a number of which first saw publication in German in mainstream newspapers and magazines) addresses how Facebook, Twitter, Snapchat, and other forms of social media work (and that broader "by-product" of the militaristic ARPANET, the internet), what they do to and with the people who use them, and how they have changed and are continuing to change cultural reality:--